Use of nanotechnology for improved pharmacokinetics and activity of immunogenic cell death inducers used in cancer chemotherapy. (2nd September 2017) - Janicka, Martyna; Gubernator, Jerzy
ABSTRACT: Introduction : Immunogenic cell death inducers (ICD inducers) are a diverse group of therapeutic molecules capable of eliciting an adaptive immune response against the antigens present on the surface of dying cancer cells. Most of these molecules suffer from low bioavailability, high toxicity and poor pharmacokinetics which limit their application. It is believed that nanotechnology, in particular nano-sized nanocarriers, can address most of the issues that limit the use of ICD inducers. Area covered : The mechanism of action of ICD inducers and their limitations is discussed. In addition, we cover the novel possibilities arising from the use of nanotechnology to improve delivery of ICD inducers to the target tissue as well as the restrictions of modern nanotechnology. Expert opinion : At present, nanocarrier formulations suffer from low bioavailability, poor pharmacokinetics and stability issues. Nonetheless, there is a tremendous future for combinatorial immune-pharmacological treatments of human tumors based on nanocarrier delivery of ICD inducers.